Development of a “Turn-on” Fluorescent Probe-Based Sensing System for Hydrogen Sulfide in Liquid and Gas Phase - Bartelmess, Juergen; Valderrey, Virginia; Rurack, Knut (Frontiers in Chemistry, 2019)
A "turn-on" fluorescence sensing system based on a BODIPY-cobaloxime complex for the detection of H2S in liquid and gas phase was developed. To that aim, two cobaloxime complexes bearing an axial pyridyl-BODIPY ligand were initially evaluated as sensitive fluorescent HS– indicators in aqueous solution. The sensing mechanism involves the selective substitution of the BODIPY ligand by the HS– anion at the cobalt center, which is accompanied by a strong fluorescence enhancement. The selection of a complex with an ideal stability and reactivity profile towards HS– relied on the optimal interaction between the cobalt metal-center and two different pyridyl BODIPY ligands. Loading the best performing BODIPY-cobaloxime complex onto a polymeric hydrogel membrane allowed us to study the selectivity of the probe for HS– against different anions and cysteine. Successful detection of H2S by the fluorescent “light-up” membrane was not only accomplished for surface water but could also be demonstrated for relevant H2S concentrations in gas phase.